The Effect of Service Quality and Promotion on Consumer Purchase Decisions at Raja Bebek - Dian Pernando Tarigan; M. Rusdi; Safaruddin Munthe (International Journal of Economics and Management Research, 2025)
This research aims to analyze the influence of service quality and promotion on consumer purchasing decisions. Service quality and effective promotional strategies are important factors in shaping consumer perceptions and purchasing interest in a product or service. The research method used is quantitative with a survey approach to 120 respondents who are active consumers in the retail sector. The data were analyzed using multiple linear regression to test the influence of the independent variable on the dependent variable. The research results show that both service quality and promotion have a positive and significant influence on purchasing decisions. Service quality that includes reliability, responsiveness and empathy, as well as targeted promotions, can increase consumer buying interest and loyalty. These findings underline the importance of companies in improving service quality and designing attractive promotional strategies to encourage sustainable consumer purchasing decisions.